Psychiatric worker and family members: pathways towards co-operation networks within psychiatric assistance services - Silvia Carbone (Mental Illness)
The family’s role in patient care was greatly altered by Law 180. This law, introduced in Italy in 1978, led to a gradual phasing out of custodial treatment for psychiatric patients. This different mindset, which views the family as an alternative to institutionalization, leads to it being seen as an essential entity in the setting up of community service dynamics. We interviewed health professionals in order to understand obstacles of collaboration between family members and mental health care workers. The goal was to uncover actions that promote collaboration and help build alliances between families and psychiatric workers. Results showed that health professionals view the family as a therapeutic resource. Despite this view, family members were rarely included in patient treatment. The reasons is: the structures have a theoretical orientation of collaboration with the family but, for nurses not are organized a few meeting spaces with family members. Services should create moments, such as multi-family groups or groups of information, managed by nurses and not only by doctors. These occasions it might facilitate the knowledge between professionals and family members.